Socialismes en Afrique - Blum, Françoise; Kiriakou, Héloïse; Mourre, Martin; Basto, Maria-Benedita; Guidi, Pierre; Pauthier, Céline; Rillon, Ophélie; Roy, Alexis; Vezzadini, Elena (54, 2021)
This book provides an overview of international research on socialisms in Africa. It brings together theoretical debates about the forms of socialism found in Africa, their intellectual roots, as well as concrete experiences, both in cities and in the countryside, from cooperatives, neighborhood committees to reeducation camps and more. It also covers Africa's relations with the Soviet Union, the People's Democracies, Cuba, China, and Israel. The authors set out to give the study of African socialisms a place in the more general field of the history of socialism, as well as in that of the Cold War.